2014
DOI: 10.1007/s00134-014-3361-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-pulmonary infections but not specific pathogens are associated with increased risk of AKI in septic shock

Abstract: This study demonstrates that the presence of septic AKI varies significantly based on the site of infection but not the type of causative organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…After multivariable analysis, no specific type of pathogen was associated with increased septic AKI risk compared to others. [18] On the other hand, another study did identify a higher number of positive blood cultures, especially gram-negative bacilli and fungi, in septic AKI patients compared to septic patients who did not develop AKI. [17] Additionally, several clinical characteristics differ between patients with septic AKI and those with non-septic AKI.…”
Section: Sepsis and Aki: Timing And Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…After multivariable analysis, no specific type of pathogen was associated with increased septic AKI risk compared to others. [18] On the other hand, another study did identify a higher number of positive blood cultures, especially gram-negative bacilli and fungi, in septic AKI patients compared to septic patients who did not develop AKI. [17] Additionally, several clinical characteristics differ between patients with septic AKI and those with non-septic AKI.…”
Section: Sepsis and Aki: Timing And Risk Factorsmentioning
confidence: 99%
“…[18] Additionally, a prospective observational international study of 1753 patients, showed that patients with septic AKI showed a trend towards higher chances of recovery and dialysis independence compared to non-septic AKI patients even though they had higher risk of death and longer hospital length of stay. [85]…”
Section: Rehabilitation and Follow Upmentioning
confidence: 99%
“…[3] While research has attempted to determine the severity of this condition in order to treat patients appropriately, little is known about how the anatomical site of infection related with clinical outcomes in sepsis-associated (SA)-AKI patients. [4,5] The Sepsis 3.0 criteria define sepsis as a life-threatening organ dysfunction caused by dysregulation in a host's response to infection. [6] In other words, the primary driver of mortality in sepsis is the systemic infl ammatory response, and this response is triggered by uncontrolled infection arising from a specifi c anatomical source, which may infl uence the progression and clinical outcome of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Renal function impairment is a frequent condition during septic shock with an incidence of acute kidney injury (AKI) ranging from 55 to 73% [ 1 3 ]. It is independently associated with mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%